2017
DOI: 10.1039/c6lc01556e
|View full text |Cite
|
Sign up to set email alerts
|

Integration of digital microfluidics with whispering-gallery mode sensors for label-free detection of biomolecules

Abstract: We present a multi-sensor chip comprising an array of whispering-gallery mode (WGM) micro-goblet lasers integrated into a digital microfluidic (DMF) system. In contrast to earlier demonstrations, the lasers are fabricated from dye-doped poly-methyl methacrylate (PMMA) at low cost using spin-coating, mask-based optical lithography, wet chemical etching, and thermal reflow techniques. Pumping and read-out of the devices is accomplished via simple free-space optics, thereby allowing large-scale sensor arrays to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…However, it was shown that the closed (or two-plate) DMF platforms are capable of performing more versatile operations on droplets (such as moving, splitting and merging) compared to open DMF platforms, especially in EWOD-based DMF 7 . The closed EWOD-based DMF platforms were also successfully employed in isolation of bio-entities such as proteins and cells 8 10 . In these systems, bio-entities are generally encapsulated in droplets sandwiched between top and bottom plates containing microwells and electrodes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that the closed (or two-plate) DMF platforms are capable of performing more versatile operations on droplets (such as moving, splitting and merging) compared to open DMF platforms, especially in EWOD-based DMF 7 . The closed EWOD-based DMF platforms were also successfully employed in isolation of bio-entities such as proteins and cells 8 10 . In these systems, bio-entities are generally encapsulated in droplets sandwiched between top and bottom plates containing microwells and electrodes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Further improvements are possible by optimizing the functionalization protocol to achieve higher density of receptor molecules, or by optimizing resonator dimensions to increase the overlap of the resonance modes with the surrounding [4]. Furthermore, active analyte agitation during measurements can accelerate response times, for example by using digital microfluidics or continuous flow systems [41][42][43]. In the future, the concept of localized dispensing may be extended to selective functionalization of resonators within a large-scale array to enable simultaneous detection of multiple target molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Wondimu et al developed WGM optical microcavity‐based label‐free biosensing incorporated in a digital microfluidic system with demonstrated streptavidin detection. [ 198 ] However, the cavities are not silicon‐based but made of polymethyl methacrylate (PMMA), which require bulky instruments (i.e., a high‐power pump laser and spectrometer) and optical focusing with free‐space optical components for measurements.…”
Section: Laboratory Prototypes Toward Poc Applicationsmentioning
confidence: 99%